Implementasi SIASN Dalam Digital Era Governance: Tinjauan Sistematis Transformasi Layanan Manajemen ASN - Lasmaria Agustina; Asropi (PT. Alahyan Publisher Sukabumi, 2026)
This study examines the implementation of the State Civil Service Information System (SIASN) as a digital governance innovation in Indonesia's public personnel management system. The study aims to analyze the SIASN implementation from the perspective of Digital Era Governance (DEG), identify its impacts on personnel services, explore implementation challenges, and propose a conceptual framework to improve digital governance practices. This study employed a Systematic Literature Review (SLR) following PRISMA guidelines. Twenty empirical articles indexed in the Sinta and Scopus databases, published between 2022-2026, were systematically selected and analyzed using thematic synthesis techniques. The findings indicate that SIASN contributes significantly to administrative integration, service efficiency, transparency, and the reduction of manual procedures through the principles of Reintegration and Need-based Holism. However, several challenges remain, including data synchronization issues, digital literacy disparities, infrastructure limitations, system instability, and organizational resistance to digital transformation. This study proposes a SIASN Digital Governance Maturity Framework that integrates technological, organizational, and governance dimensions within the DEG perspective. The study contributes theoretically by extending Digital Era Governance concepts into public personnel systems and practically by providing policy recommendations to improve digital public services in Indonesia.